Estágios obrigatórios em cursos de pedagogia a distância : tensões e possibilidades - Santos, Maria da Conceição Oliveira (2017)
This study focuses on the internship program within an Undergraduate Distance Learning Education Programs, seeking to understand how former students, now active teachers, perceive this internship and tries to identify tensions and contributions to the academic training of this teacher/educator. As a qualitative research in its core, with the use of questionnaire and interviews to collect data and main theoretical reference brings theory/practice concepts, as well as pre-teaching internship programs and distance learning. Bibliographic review showed that monitored internship is the most important phase of teacher training, when students can approach professional teaching practice and have the opportunity to reflect upon theories visited during their program as well as creating their own. The choice for distance learning programs is a result of a cost-benefit analysis, which includes schedule flexibility, affordable tuition fees, compliance with legal educational requirements and teaching career development. Monitored internship offers multiple formative possibilities, and is part of a context of expansion of Higher Education Institutions (HEI) in Brazil, and at the same time, of commodification of higher education. A great number of participants of this research reported they have not accomplished the legal requirement of completing internship time in Basic Education schools, and also that the monitoring and follow up services provided by the HEI is insufficient for proper teacher training. The articulation between theory and practice for these students will only make sense after the end of the program, while the internship (if carried) brings new meanings for the practice of these new professionals. Such scenario shows the problems of the uncontrolled expansion of Distance Learning Education Programs in Brazil in the latest years, by the huge number of programs that are offered by private HEIs, and reveals the need for revision of the procedures and provisions of this educational format.